Pengaruh Financial Literacy, Religiusitas, Investment Knowledge terhadap Pengambilan Keputusan Investasi melalui Investment Intention sebagai Variabel Intervening - Besri, Almaidah Ana Oktavia; Husni, Tafdil; Rahim, Rida (SAFE-Network, 2023)
Investment decisions are a person's actions to determine and allocate capital to certain assets or companies with the aim of obtaining profits in the future. In making investment decisions one must have financial knowledge to plan investments properly. This is important so that the investment decisions taken have clear and directed objectives. This research aims to find out how financial literacy, religiosity and investment knowledge influence investment decision making through investment intention as an intervening variable. This study uses a quantitative approach, namely by distributing questionnaires as a means of collecting data. The number of respondents was 160 people who were investors in Padang City, and the selection of respondents was carried out using a saturated sampling method (census). Structural Equation Modeling (SEM) was chosen as the data analysis method using the SmartPLS 4 application as an analysis tool. In the research, the results showed that financial literacy, religiosity, investment knowledge and investment intention had a positive effect on investment decisions. Likewise, financial literacy and investment knowledge have a positive effect on investment decisions through investment intention. However, religiosity does not have a positive effect on investment decisions through investment intention.